“Brain death”, autonomy, and the future of organ transplantation - Iftime, Oana (Acta Bioethica, 2019)
Autonomy and its companion, informed consent is regarded as fundamental in contemporary medical ethics. Still, the individuals are deprived of the possibility to make a genuinely informed choice with respect to organ donation in the event of “brain death”. It can be easily argued, scientifically speaking, that the status of the “brain dead” patients is that of living beings, able to process nutrients and drugs and even to harbour and nourish their progeny into the womb. A philosophical, not scientific distinction between the “un-meaningful” lives of the “brain dead” and “meaningful” human life underlines the “brain death” concept. Yet, the public is told that the “brain dead” are dead, i. e. lacking life. Not only that this situation collides with the principle of autonomy, but it also poses a risk for public trust in organ transplantation. It is obvious that people have certain expectancies from health care professionals and the decision makers, and finding out about such inconsistences might drive the public reject organ transplantation, with the recourse to the “brain death” concept ultimately leading to the aggravation of the organ shortage, instead of the alleviation that it was expected to bring.